2020
DOI: 10.3389/fcell.2020.567659
|View full text |Cite
|
Sign up to set email alerts
|

No Impact of Long-Term Fingolimod Treatment on Fecal Secretory Immunoglobulin A Levels in Patients With Multiple Sclerosis

Abstract: Background: Fingolimod (FTY) is a sphingosine 1 phosphate (S1P) agonist with significant effects on immune cell distribution used as an effective disease modifying therapy in multiple sclerosis (MS) patients. Animal studies have demonstrated that a dysregulation of egress of murine secretory Immunglobulin A (sIgA)+ plasmablasts from Peyer's patches in FTY-treated mice reduced fecal sIgA levels. Alterations in intestinal levels of sIgA could modify the gut microbiome and homeostasis in humans. We analyzed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Intestinal IgAs play a critical role in the defense against external pathogens and in maintaining intestinal homeostasis, as they are part of the complex system necessary to maintain the correct gut permeability [70]. However, an exploratory study showed no reduction in secretory IgA in fecal samples of people with MS after long-term treatment with FTY [71].…”
Section: Sphingosine-1-phosphate Receptor Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal IgAs play a critical role in the defense against external pathogens and in maintaining intestinal homeostasis, as they are part of the complex system necessary to maintain the correct gut permeability [70]. However, an exploratory study showed no reduction in secretory IgA in fecal samples of people with MS after long-term treatment with FTY [71].…”
Section: Sphingosine-1-phosphate Receptor Modulatorsmentioning
confidence: 99%
“…Sphingosine-1-phosphate receptor modulators [52,[66][67][68][69][70][71][72] Induction of Treg activity in the gut mucosa Inhibition of epsilon toxin-secreting Clostridium perfringens Natalizumab [75][76][77] Reduction in T-cell trafficking in the gut mucosa Anti-CD20 monoclonal antibodies [82][83][84][85] Maintenance of intestinal barrier homeostasis Increase in anti-inflammatory species and decrease in inflammatory species…”
Section: Dmt Main Effects On Gut-brain Axismentioning
confidence: 99%
“…Fingolimod treatment, which targets this receptor, resulted in the reduction in B cells and IgA production in mice. Secretory IgA concentrations in stools and saliva were equivalent in MS patients treated with fingolimod compared to GA-treated MS patients [ 162 ]. A comparison with untreated patients would be very informative.…”
Section: Treatments Targeting Iga and Microbiotamentioning
confidence: 99%